Laying the foundations of international careers research. (15th May 2020) - Mayrhofer, Wolfgang; Smale, Adam; Briscoe, Jon; Dickmann, Michael; Parry, Emma
Abstract: As an editorial to the special issue "new avenues in international careers research" this article discusses the roots of the international careers research stream, which sits at the intersection between career studies, HRM and international management. In order to support future studies in this emerging area of enquiry, we attempt to lay down the foundations of a research agenda based around what we see as the three core areas of interest: contextualised careers research, comparative careers research and careers research in internationally operating organisations. After providing some suggestions for the kinds of theoretical and methodological tools that will be required to build on these foundations, we introduce the five empirical papers that comprise this special issue.